Implementation of Brand Image and Social Media Marketing on Purchasing Decisions at The Apurva Kempinski Bali - Puteri, Putu Belinda; Marheni, Lily; Priyana, I Putu Okta (ARRUS Journal of Social Sciences and Humanities, 2024)
This study was conducted to investigate how brand image and the implementation of social media marketing effectively can increase consumer purchasing decisions on products or services in the hospitality industry. This study employed a quantitative inferential approach and was carried out at The Apurva Kempinski Bali hotel. The target population in this study includes all followers of the hotel's Instagram account and prospective consumers who want to visit the hotel. Through purposive sampling and the Slovin formula, 100 valid responses were obtained through the distribution of questionnaires. The data gathered were analyzed using multiple linear regression to determine how a strong brand image and the effective implementation of social media marketing could impact consumer choices. The results of the study reveal that a strong brand image, combined with effective social media marketing, significantly enhances consumer purchasing decisions for The Apurva Kempinski Bali's services and products. This underscores the importance of both a robust brand reputation and well-executed social media strategies in driving customer engagement and sales in the hospitality industry. This research contributes to marketing theory by highlighting both strategies influence consumer decisions. Practically, it helps The Apurva Kempinski Bali develop effective strategies for building a strong brand and using social media to attract and engage customers.